2009
DOI: 10.1373/clinchem.2008.118505
|View full text |Cite
|
Sign up to set email alerts
|

SELDI-TOF Mass Spectrometry Evaluation of Variant Transthyretins for Diagnosis and Pathogenesis of Familial Amyloidotic Polyneuropathy

Abstract: BACKGROUND:Mass spectrometric analyses are valuable for detection of transthyretin (TTR) variants, which cause familial amyloidotic polyneuropathy (FAP). However, those methods require an immunoprecipitation step with an anti-TTR antibody and are not suitable for quantitative detection. We investigated the usefulness of SELDI-TOF mass spectrometry (MS) without an immunoprecipitation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…To detect wild-type and mutant transthyretins, serum samples were analyzed by using surface-enhanced laser desorption/ionization time-of-flight mass spectrometry with the Q10 ProteinChip (Bio-Rad, Hercules, CA, USA), a strong anion exchange array with quaternary amine functionality, as described previously. 19 …”
Section: Nephelometry To Measure Serum Transthyretin Concentrations Amentioning
confidence: 99%
“…To detect wild-type and mutant transthyretins, serum samples were analyzed by using surface-enhanced laser desorption/ionization time-of-flight mass spectrometry with the Q10 ProteinChip (Bio-Rad, Hercules, CA, USA), a strong anion exchange array with quaternary amine functionality, as described previously. 19 …”
Section: Nephelometry To Measure Serum Transthyretin Concentrations Amentioning
confidence: 99%
“…The lower limit of separation minimum mass difference between two molecules could be separated in this system is thought to be about 15 Da, based on the present and previous studies. 5 We were able to separate Leu55Pro and Ala25Ser mutants, which theoretically have a mass shift of 16 Da from WT TTR but were not able to separate Lys35Asn and Ile107Val mutants, which theoretically have a mass shift of 14 Da from WT TTR. 5 SELDI-TOF MS could not separate the atypical TTR variants, whereas succeeded in detecting most variant TTRs, including the common Val30Met TTR.…”
Section: Resultsmentioning
confidence: 73%
“…4 We previously reported a convenient SELDI-TOF MS method that does not require an immunoprecipitation step to detect several types of variant TTR. 5 In this study, we evaluated the clinical usefulness of SELDI-TOF MS for diagnosis of TTR-related amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of total TTR is conjugated and posttranslationally modified in serum as shown by electrospray ionization (ESI)-mass spectrometry (MS)/MS (Ueda et al, 2009). In this study, we used isoelectric focusing and TTR western blotting and found that nitric oxide-mediated modification of serum TTR occurs when reacted with the MPO/H 2 O 2 system (Figure 4).…”
Section: Discussionmentioning
confidence: 88%